Molecular phylogeny of Asian pipesnakes, genus Cylindrophis Wagler, 1828 (Squamata: Cylindrophiidae), with the description of a new species from Myanmar - Bernstein, Justin M.; Bauer, Aaron M.; Mcguire, Jimmy A.; Arida, Evy; Kaiser, Hinrich; Kieckbusch, Max; Mecke, Sven (Zootaxa, 2020)
Cylindrophis is a genus of secretive, semi-fossorial, non-venomous snakes comprising 14 species, characterized by a generally cylindrical body, uniform scales (with barely enlarged ventrals), and vestiges of pelvic and limb bones, the latter terminating in a claw lateral to the vent. We reconstructed a concatenated molecular phylogeny of seven taxa of Cylindrophis taxa based on one nuclear (R35) and two mitochondrial (16S, ND2) genes. Analyses recovered the Sri Lankan endemic C. maculatus as sister to all other sampled Cylindrophis. The mainland Southeast Asian species C. burmanus and C. jodiae form successive sister lineages to a monophyletic Wallacean island group containing C. boulengeri, C. isolepis, and C. yamdena. We also describe a new species of Cylindrophis, morphologically similar to C. burmanus, from Kachin State in northern Myanmar. Cylindrophis slowinskii sp. nov. is distinguished from all congeners by the following combination of characters: 19 dorsal scale rows at midbody, 216–220 ventrals, eight subcaudals, a dark venter with > 60 very narrow diffuse pale blotches, and a pale bar running along the posterior border of the prefrontals. In our phylogeny, the new species is strongly supported as the sister species of C. burmanus. It is the 15th currently recognised species in the genus, and the fourth from mainland Southeast Asia.